Stressors Due to Handling Impair Gut Immunity in Meagre (Argyrosomus regius): The Compensatory Role of Dietary L-Tryptophan - Asencio-Alcudia, Gloria; Andree, Karl B.; Giraldez, Inmaculada; Tovar-Ramirez, Dariel; Alvarez-González, Alfonso; Herrera, Marcelino; Gisbert, Enric (Frontiers in Physiology, 2019)
In the context of intensive aquaculture, meagre (Argyrosomus regius) is one of the most important new aquaculture species in Southern Europe and several studies are focusing on the optimization of its culture. Nevertheless, stressors like handling during transport or culture maintenance may affect the immune system impairing some immune responses or provoking cellular damage. One strategy that has been used to avert this type of negative stress response is the supplementation of amino acids to improve resistance to stress. In this experiment, meagre (105 ± 2.6 g, mean ± standard deviation) juvenile were fed for a period of 7 days with two diets, the first a commercial diet supplemented with 1% tryptophan (Trp) and the same commercial diet without tryptophan supplementation (control group). A two-way experimental design was conducted in order to compare the effects of two types of handling stressors (air exposition and confinement/netting) on fish and evaluate the effects on gene expression of selected gut immunity markers: i) innate immune response processes: c3 complement (c3), lysozyme (lys) and cyclooxygenase (cox2); ii) humoral immune response processes: interferon type 1 (ifn1), mx protein (mxp), interleukin 1b (il-1b), tumor necrosis factor 1a (tnf1a) and interleukin 10 (il-10); (iii) antimicrobial peptides: defensin (def), hepcidin (hep), piscidin (pis) and a marker for mitochondrial respiration: glyceraldehyde 3-phosphate dehydrogenase (gapdh). Samples were collected and analyzed at 1 and 6 h post-stress treatments. Results showed that the air exposure test has a up-regulated gene expression at 1 h post stress (hps) test in fish fed 1% Trp for c3, lys, cox2, ifn1, mxp, il-10 and gapdh, and il-1b and pis at 6 hps. Confinement/netting test showed a up-regulated gene expression for c3 and mxp, and down-regulated gene expression for cox2, ifn1, il-1b, tnf1a, il-10, def, hep and gapdh for fish fed 1% Trp in both post-stress times. According to the present study, dietary supplementation with 1% Trp may be considered as a proper nutritional strategy for preventing and/or alleviating handling stress, particularly to air exposure treatment.